The Influence of Big Data, Compliance Risk Management, and Business Intelligence on Tax Compliance - Astuti, Puji; Rapina, Rapina; Meythi, Meythi; Joni, Joni (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
Advances in information technology have brought significant changes to various sectors, including tax administration. The use of technologies such as Big Data, Compliance Risk Management (CRM), and Business Intelligence (BI) is believed to improve taxpayer compliance by analysing large amounts of data and managing tax risks more effectively. This study aims to analyse the influence of Big Data, CRM, and BI on tax compliance levels in Indonesia. A quantitative approach was used, with data collected through questionnaires from Account Representatives at the Regional Office (Kanwil) of the Directorate General of Taxes (DJP) West Java I (Jabar I). The data was analysed using the Partial Least Squares Structural Equation Modelling (PLS-SEM) model. The results of the study indicate that all three variables have a significant influence on tax compliance, with CRM as the dominant factor influencing taxpayer compliance. This study contributes to the development of technology-based taxation strategies and policy recommendations for tax authorities in improving tax management efficiency in the digital era.